Application and Optimization Strategies of Social Media Platforms in College Students’ Ideological and Political Education - Yang, Xiaotong (International Journal of Social Sciences and Public Administration, 2025)
With the rapid development of social media, college students’ ideological concepts and behaviors are significantly influenced. Effectively integrating social media into ideological and political education can not only align with young people’s lifestyles but also enhance educational effectiveness. This paper analyzes the current application and challenges of social media in ideological and political education from the perspective of its dissemination characteristics and proposes optimization strategies. The aim is to promote innovation in the methods and content of higher education’s ideological and political education, enhancing the timeliness and relevance of education.